O fonoaudiólogo como facilitador da relação mãe-bebê de alto risco - Aquino, Maria de Fátima Prudente de (2005)
This study proposes that the speech therapist be a facilitator element of relationship between mother and baby of high risk, because sensorial involvement is indispensable for the psychical development of the baby and to the emergence of his oral language. The proposal of this study appeared since the evidence that many mothers of premature newborn babies in Newborn and Pediatric Intensive Treatment Unit of Hospital das Clínicas Samuel Libânio de Pouso Alegre/MG , were not able to identify corporal expression of their children and did not achieved the sensorial involvement during clinical evolution and qualification of babies to exclusive oral alimentation. In this manner, the proposal of this work is the investigation of mediation as a tool of facilitator intervention of the relationship mother and baby of high risk through technical instruments relationed with newborn care, and the shelter of mother with her anguishes and fears. The technicals tools used in this study were: the correct position of the baby; offering of smell and taste stimulus, the elicitation of alimentation and defense reflections, Nutritive Suction through sounding lead-finger technique; the No Nutritive Suction, the offering of pleasant touch, gentle opening of incubator porthole and the luminosity control through black using. Along the study it was evident that the speech therapy mediation fortifies the trust of mother in herself, and in an ability to become available to her child and recognize him as a love object that demands care, reflecting in the sensorial involvement offered by her. The technical instruments, in this context, become near mother and baby and contribute to the mother´s interest and her participation in the work of assistance the babies alimentation and cares relationed with hearing